The tragedy of Macbeth [videorecording (DVD)] - Polanski, Roman; Finch, Jon, 1941-2012; Annis, Francesca, 1945-; Shaw, Martin, 1945- (Criterion collection, 2014)
Roman Polanski imbues his unflinchingly violent adaptation of William Shakespeare's tragedy of ruthless ambition and murder in medieval Scotland with grit and dramatic intensity. Jon Finch and Francesca Annis star as a decorated warrior rising in the ranks and his driven wife, scheming together to take the throne by any means.